Role-Play Preceded by Fieldwork in the Teaching of Pharmacology: from “Raw Sap” to “Elaborated Sap” - Gotardelo,Daniel Riani (2017)
ABSTRACT Background: The task of teaching abilities, attitudes and knowledge, which can sometimes be complex, related to the safe and efficient use of medications, stands as a great challenge faced by medical schools nowadays. The role of the prescriber, therefore, who promotes the rational use of medication at undergraduate level gains importance in professional training, with a direct impact on public healthcare. In this context, the implementation of teaching methods that allow an active, critical and reflexive medical training for students is desirable in order to enable them to develop the skills required to manage the main pharmacological classes used by the general practitioner. We intend to describe and analyze role-play preceded by fieldwork as an educational strategy. Methods: Following the fieldwork regarding the utilization of the main pharmacological classes used in primary healthcare, 5-6 groups of students prepared scripts and staged role-plays involving practical aspects of pharmacokinetics, pharmacodynamics, side effects, and potential drug interactions regarding the main drug types. The intervention was assessed using students’ responses to questionnaires coupled with Likert scales, the Dundee Ready Education Environment Measure (DREMM) and semi-structured interviews. There was a correlation between participation in teaching practice and performance in multiple-choice questions in the final course evaluation. Results: All students felt involved and motivated in the activity. 78.5% strongly agreed and 19% partially agreed that the method allowed reflection on knowledge, abilities and attitude, all important to professional practice regarding rational therapeutic prescribing. The DREMM revealed a score of 129.23, consistent with a more positive learning environment in a reliable sample (Cronbach's alpha=0.86). Analysis of the open interviews allowed us to infer that the students considered the method efficient, dynamic, fun, and enjoyable, which enabled greater understanding and consolidation of the content. The strategy was considered stimulating regarding group activities, with active participation. Furthermore, it allowed students an opportunity to experience their future professional reality. The main weaknesses found were the unequal involvement of individuals in some groups and the great length of time spent in the preparation of activities. In the final exam, the students who participated in the intervention had, on average, a higher performance than those who did not take part in it. However, there was no statistically significant difference. Discussion: Role-play preceded by fieldwork proved to be a promising pedagogical strategy and may be used in other basic sciences.